Recent advance of metal borohydrides for hydrogen storage - Liu, Jianjun; Ma, Yong; Yang, Jinggang; Sun, Lei; Guo, Dongliang; Xiao, Peng (Frontiers in Chemistry, 2022)
Hydrogen energy is an excellent carrier for connecting various renewable energy sources and has many advantages. However, hydrogen is flammable and explosive, and its density is low and easy to escape, which brings inconvenience to the storage and transportation of hydrogen. Therefore, hydrogen storage technology has become one of the key steps in the application of hydrogen energy. Solid-state hydrogen storage method has a very high volumetric hydrogen density compared to the traditional compressed hydrogen method. The main issue of solid-state hydrogen storage method is the development of advanced hydrogen storage materials. Metal borohydrides have very high hydrogen density and have received much attention over the past two decades. However, high hydrogen sorption temperature, slow kinetics, and poor reversibility severely restrict its practical applications. This paper mainly discusses the research progress and problems to be solved of metal borohydride hydrogen storage materials for solid-state hydrogen storage.